Prolapse of the third eyelid gland in dogs - Raymundi, Andressa Cardoso; Menezes, Bárbara Fernandes; Veloso, Claudia Liliane Mendes; Vieira, Julissandra Oliveira Cândido; Sousa, Leticia Ferreira; Rodrigues, Maria Eduarda Leal; Castro , Thaiz Alves Lopes Guimarães de; Silva, Thays Borges (Seven Editora, 2023)
Prolapse is the protrusion of the gland of the third eyelid, in which, when it is exposed and moves out of its normal position, it is probably caused by laxity of the appendages, trauma, or primary or secondary adenitis. It manifests itself more frequently in young animals and has breeds more predisposed to its appearance such as English Bulldog, Cocker, Basset hound, Beagle, Pekingese and Boston. Clinical signs are the appearance of a reddish-pinkish, bulky mass located in the nasomedial corner of the eye, mucoid or serous discharge, and conjunctivitis. Diagnosis is made based on anamnesis, physical examination, and patient history. Treatment is based on fluorescein testing to identify corneal ulcers, if corneal ulcers are not identified, prophylactic preoperative management with antibiotic and/or anti-inflammatory eye drops, with subsequent repositioning of the third eyelid gland. The prognosis is good according to the technique chosen for each case and with good management during the patient's postoperative period. DOI:https://doi.org/10.56238/interdiinovationscrese-093